The use of swaps by local administrations: the case of Italian regions, 2007–2014 - Giulia Fantini (Journal of Public Budgeting, Accounting & Financial Management, 2020)
Swaps have been extensively employed by governments and local administrations to manage their debts and related costs, but the financialisation of the public sector has had insufficient attention in the literature. This study creates the first database on swaps underwritten by Italian regions to investigate their impact on total debt and their strategic use (i.e. to finance discretional debt). Panel data results show that regions with higher debt exhibit a higher interest rate exposure and have employed derivatives for strategic purposes in their attempts to counterbalance the reduced resources received from the central state, in line with other countries’ experiences.